Understanding cultural diversity in the early years - Baldock, Peter (Los Angeles : Sage, 2010)
Taking the discussion about cultural diversity beyond the usual topics of anti-racism & inclusion but without overlooking these issues, this book considers current debates around the alleged failure of multiculturalism, & encourages practitioners to use their own cultural backgrounds & experiences as a way of developing their teaching.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Early childhood education -- Great Britain; Multicultural education -- Great Britain; Electronic books